Preparation of Terminalia catappa Shell Based Activated Carbon by Microwave Assisted Chemical Activation - awitdrus, awitdrus (Talenta Publisher, 2019)
Activated carbon was prepared from Terminalia catappa shells using microwave asissted KOH activation. The ratio of mass percentages of Terminalia catappa and KOH were 4:1, 4:2, and 4:3. Terminalia catappa based activated carbon was prepared by KOH activation at the room temperature for 24 hours and followed by microwave irradiation at the out put power of 630 Watt for 20 minutes. The physical properties of activated carbon i.e. surface morphology, micro structure, and BET surface area were characterized by electron scanning microscope, X-ray diffraction and N2 adsorption-desorption isotherm at 77K, respectively. The highest BET surface area was 312 m2/g with adsorption of activated carbon towards methylene blue by 84.4 mg/g. The BET surface area was directly correlated with the stack height (Lc) of the activated carbon.